Semen Discard Rate at Fresh and Post-Thaw Stages in Indian Riverine Buffalo (Bubalus bubalis) - Bisla, Amarjeet; Rautela, Rupali; Katiyar, Rahul; Kumar, Abhishek; Ghosh, Subrata Kumar; Srivastava, Neeraj (The Indian Journal of Animal Reproduction, 2022)
The quality of spermatozoa at post-thaw stage depends on many factors including the level of lipid per-oxidation (LPO) and the antioxidant profile of the ejaculates at fresh stage. Thus, the present investigation was done to evaluate discard rate of semen ejaculates at fresh and post-thaw stages in association with various semen quality parameters in Murrah buffalo.  A total of 79 ejaculates from seven Murrah buffalo bulls formed part of the study. Following application of rigorous prescribed selection criteria it was observed that 17.72% (14/79) ejaculates were discarded at fresh stage due to poor quality. The initially selected ejaculates were processed for cryopreservation as per the minimum standard protocols. The study show satisfactory results for 31 (47.69%) samples for inclusion in the further AI programme (discard rate of 52.31% (34/65) at post thaw. The mean post-thaw motility (PTM; %) of the passed ejaculates was found to be 44.2±1.0. In conclusion, study results show efforts to minimize LPO and enhance total antioxidant capacity (TAC) at various processing stages shall play a vital role in reducing discard rate of the semen samples in buffalo bulls.
Keywords: Murrah; Post-thaw; Acrosome integrity; Freezability; ROS